The Influence of Action Video Games on Attentional Functions Across Visual and Auditory Modalities - Wu, Xia; Jiang, Ying; Jiang, Yunpeng; Chen, Guodong; Chen, Ying; Bai, Xuejun (Frontiers in Psychology, 2021)
Attention can help an individual efficiently find a specific target among multiple distractors and is proposed to consist of three functions: alerting, orienting, and executive control. Action video games (AVGs) have been shown to enhance attention. However, whether AVG can affect the attentional functions across different modalities remains to be determined. In the present study, a group of action video game players (AVGPs) and a group of non-action video game players (NAVGPs) selected by a video game usage questionnaire successively participated in two tasks, including an attention network task-visual version (ANT-V) and an attention network task-auditory version (ANT-A). The results indicated that AVGPs showed an advantage in orienting under the effects of conflicting stimuli (executive control) in both tasks, and NAVGPs may have a reduced ability to disengage when conflict occurs in visual task, suggesting that the AVGs can improve guidance toward targets and inhibition of distractors with the function of executive control. AVGPs also showed more correlations among attentional functions. Importantly, the alerting functions of AVGPs in visual and auditory tasks were significantly related, indicating that the experience of AVGs could help us to generate a supramodal alerting effect across visual and auditory modalities.